Chapter 6 On representing anchored parentheses in syntax - Kluck, Marlies (De Gruyter, 2015)
The paper is organised as follows. In order to establish which kinds of parentheses should be considered 'anchored', I present a global overview in §2. This is followed by a discussion of the core properties of anchored parentheses, focusing on the relation between anchor and parenthesis, and their 'specificational' interpretation. §3discusses anchored parenthesis in the domain of parallel construal, and shows why the Kosterian colon phrase is not sufficient to account for them. In §4, I elaborate onthe structural independence of parentheticals in the context of De Vries' syntactic approach, suggesting a parenthetical version of the colon phrase to account for anchored parenthesis. §5 is a brief discussion of two implications (or: complications) of this analysis. §6 concludes the paper.